Smart nanogels for cancer treatment from the perspective of functional groups - Yu, Jiachen; Liu, Yuting; Zhang, Yingchun; Ran, Rong; Kong, Zixiao; Zhao, Duoyi; Liu, Minda; Zhao, Wei; Cui, Yan; Hua, Yingqi; Gao, Lianbo; Zhang, Zhiyu; et al. (Frontiers in Bioengineering and Biotechnology, 2024)
Nanogel has good biocompatibility and is an ideal 3D network chemotherapy drug system with high water content, which has been widely used in drug sustained sustained drug release field. Among them, the assembly of nanogels through functional groups and intelligent response through various external stimuli are the two most important links for nanogels to play their roles. In this article, we summarized the drug loading methods of various types of nanogels based on different functional groups, and introduced the latest progress of smart hydrogels.